Expression of IGFs during postnatal development of Longissimus dorsi muscle and its relationship with meat quality traits in Nanyang cattle - ZHANG, XIAOHUI; QI, YANXIA; PANG, YOUZHI; WANG, DANDAN; GUO, ZHAO (The Indian Journal of Animal Sciences, 2013)
The IGFs pathway plays important roles in body energy metabolism and muscle mass regulation. The expressions of IGFs in Longissimus dorsi muscle were analyzed by qRT-PCR at postnatal 3, 6, 12, 18 and 24 month-old. The expression of IGF-I, IGF-II, IGF-IR, IGF-IIR, IGFBP1 and IGFBP3 showed significant decreasing tendency during the postnatal Longissimus dorsi muscle development, while the expression of IGFBP2, IGFBP4, IGFBP5 and IGFBP6 had no significant changes from postnatal 3 to 24 month-old in Nanyang cattle. The expression of IGF-IIR, IGFBP5 and IGFBP6 had significant positive correlation with IMF and expression of IGF-II had significant negative correlation with meat flavor trait of Longissimus dorsi muscle in 24 month-old Nanyang cattle. This study indicated that endogenous IGFs pathway played critical roles in regulation of skeletal muscle development, IMF accumulation and meat sensory traits.